2014
DOI: 10.1681/asn.2013101110
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Dynamics in AKI to CKD Progression

Abstract: Stemming from the recent and robust clinical data confirming that AKI does indeed increase the likelihood of developing CKD (reviewed by Chawla and Kimmel 1 ), numerous preclinical studies have offered insight into how the transition from AKI to CKD occurs. However, our understanding of this multifactorial process is incomplete. This knowledge is critical if we are to advance therapeutic strategies to combat the detrimental progression of renal injury. The development of CKD is thought to be promoted by an abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…It has been previously shown that BNP can inhibit cardiac inflammation induced by IRI (Hu et al, 2014). We also observed macrophage infiltration at an early stage of IRI (24 h after reperfusion) and noticed a pro-inflammatory phenotype of the macrophages (Kinsey, 2014;Huen and Cantley, 2015). However, the number of macrophages declined after BNP intervention.…”
Section: Discussionsupporting
confidence: 59%
“…It has been previously shown that BNP can inhibit cardiac inflammation induced by IRI (Hu et al, 2014). We also observed macrophage infiltration at an early stage of IRI (24 h after reperfusion) and noticed a pro-inflammatory phenotype of the macrophages (Kinsey, 2014;Huen and Cantley, 2015). However, the number of macrophages declined after BNP intervention.…”
Section: Discussionsupporting
confidence: 59%
“…During the early stages of IRI, macrophages have a proinflammatory role in mediating injury; during the late phase, they transform themselves into the anti-inflammatory phenotype to repair injury. 37,38 In this study, the increase in CD68þ macrophages could be mitigated by EPO treatment after IRI.…”
Section: Discussionmentioning
confidence: 62%
“…For example, macrophages deliver reparative Wnt7b to tubular epithelia, enhancing proliferation and restoration of a functioning nephron. 58,59 A summary of the most recent findings for other therapeutic targets is presented in Tables 1 and 2.…”
Section: What Aspects Of Repair Can Be Targeted Therapeutically?mentioning
confidence: 99%